Pengaruh Persepsi Harga, Citra Merek, Kualitas Produk Terhadap Loyalitas Pelanggan - Wa Ode Trinita Ratu Kobadiana; Meylani Tuti (Revenue Journal: Management and Entrepreneurship, 2026)
This study addresses the intensifying competition in fast-moving consumer industries, forcing market leaders to strategically manage external and internal factors that reinforce long-term consumer retention. The primary objective of this research is to analyze the empirical effects of price perception, brand image, and product quality on customer loyalty toward the Indomie brand. Utilizing a quantitative methodology with an associative design, data were gathered via online questionnaires from 161 active consumers selected through purposive sampling. The structural model was evaluated using Partial Least Squares-Structural Equation Modeling (PLS-SEM) managed through the SmartPLS software. The analytical results demonstrate that price perception, brand image, and product quality exert positive and statistically significant impacts on customer loyalty, with product quality identified as the most prominent determinant. Conclusively, these findings imply that sustaining rigorous product standards, reinforcing a reputable brand reputation, and aligning price structures with consumer benefits are critical corporate strategies to prevent customer switching and secure a sustainable competitive advantage